2011
DOI: 10.4103/0253-7613.75670
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic activity of Nymphaea alba Linn. in mice as experimental models of anxiety

Abstract: Objective:The aim of the present work was to evaluate the anxiolytic effect of an ethanolic extract of Nymphaea alba Linn. in mice.Materials and Methods:The elevated plus maze test (EPMT), light and dark test (L and DT) and open field test (OFT) were used to assess the anxiolytic activity of the ethanolic extract of N. alba Linn. in mice. In addition, aggressive behavior and motor coordination was also assessed by foot shock induced aggression test (FSIAT) and rota rod test (RRT). Diazepam 1 mg/kg served as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 15 publications
3
49
0
2
Order By: Relevance
“…This portrays a manifestation of anxiety. [34] The open field model examines related psychomotor performance, normal aversion and behavioral aspect of [35] due to thoughts of imminent threat. The locomotive activity of the mice significantly (P < 0.05) increased at extract doses of 200 mg/kg and 600 mg/kg across the square of the open field, higher at these doses of the extract compared to diazepam and the normal saline group.…”
Section: Discussionmentioning
confidence: 99%
“…This portrays a manifestation of anxiety. [34] The open field model examines related psychomotor performance, normal aversion and behavioral aspect of [35] due to thoughts of imminent threat. The locomotive activity of the mice significantly (P < 0.05) increased at extract doses of 200 mg/kg and 600 mg/kg across the square of the open field, higher at these doses of the extract compared to diazepam and the normal saline group.…”
Section: Discussionmentioning
confidence: 99%
“…Many biological activities, including anticancer and antiviral, has been attributed to gallic and ellagic acid which are widely present in N. lotus [8]. Our previous study also showed that the aqueous extract of N. lotus is rich in phytochemicals such as proanthocyanidins, phenolics, tannins, flavonoids and saponins [9].…”
Section: Introductionmentioning
confidence: 88%
“…Both In situ and In vivo studies have shown that the plant exudates contain polysaccharides and proteins which make it efficient for gummosis [49]. This property of P. laevigata can be explored further to be used in confectionary, sauces, jellies, spray drying of juices, bakery products, adhesives, fixatives, micro encapsulations, wood furniture, gels, cosmetics, and various other industrial uses.…”
Section: Applications In Industrymentioning
confidence: 99%